A curvature-compensated bandgap voltage reference with a temperature coefficient trimming circuit. (January 2022) - Li, Tiangang; Gao, Bo; Zhao, Xin; Gong, Min
Abstract: This paper presents an advanced topology of bandgap voltage reference (BGR) which consists of a novel curvature-compensated circuit and a current-mode trimming circuit. A positive-temperature-coefficient (positive-TC) nonlinear term is produced in the difference between the base-emitter voltages of two bipolar junction transistors ( Δ V BE ) to realize the high-order curvature compensation. The Δ V BE is generated by adding a negative-TC current into the bandgap core. Owing to the compensated Δ V BE, the BGR could be fine-tuned by an innovative current-mode trimming circuit which takes less area and achieves a larger trimming range. Benefiting from the trimming circuit, the PVT stabilities of proposed BGR are improved. Designed in a 0.18 μ m HVCMOS process, the BGR occupies an active area of 267 μ m × 226 μ m . The post-layout simulation results show the BGR reaches a low TC of 1.64 ppm/ ∘ C in a wide range of -55 °C to 125 °C.